2020
DOI: 10.1007/s40789-020-00306-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial degradation of coal discard and geologically weathered coal

Abstract: The biodegradation of coal discard is being intensively studied in South Africa in an effort to develop passive methods for the successful revegetation and rehabilitation of waste dumps, to mitigate pollution, and facilitate mine closure. Bacteria were isolated from slurries of coal tailings and diesel-contaminated soil, screened for coal biodegradation competence, characterized, and the colonization and degradation of coal discard and geologically weathered coal investigated using individual isolates and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…These isolates were Proteus strain ECCN 20b, Proteus strain ECCN 23b and Serratia strain ECCN 24b. Interestingly, Serratia strain ECCN 24b, either alone or in consort with Citrobacter strain ECCN 19b and Exiguobacterium strain ECCN 21b, was previously shown to be most effective in coal bioconversion [40]. Furthermore, and in corroboration with results from other studies, Serratia strain ECCN 24b was able to solubilise insoluble phosphate [60,61] and potassium [62].…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…These isolates were Proteus strain ECCN 20b, Proteus strain ECCN 23b and Serratia strain ECCN 24b. Interestingly, Serratia strain ECCN 24b, either alone or in consort with Citrobacter strain ECCN 19b and Exiguobacterium strain ECCN 21b, was previously shown to be most effective in coal bioconversion [40]. Furthermore, and in corroboration with results from other studies, Serratia strain ECCN 24b was able to solubilise insoluble phosphate [60,61] and potassium [62].…”
Section: Discussionsupporting
confidence: 76%
“…Databases thus generated yield invaluable information about indicator species [59]. To determine the phylogenetic relationship between coal-degrading bacteria isolated earlier [40] and the diverse array of PGP bacteria contained in the NCBI GenBank database, basic bioinformatics was used to determine the genetic relatedness of the 16S rRNA gene sequences while conventional biochemical assays were used to screen for putative PGP characteristics. Strains from seven genera of coal-degrading bacterial isolates utilised in the present study showed ≥ 99% homology with reference gene sequences of PGP bacteria contained in the NCBI GenBank database.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations